Coprolites in natural traps: direct evidence of bone‐eating carnivorans from the Late Miocene Batallones‐3 site, Madrid, Spain. (27th July 2021) - Abella, Juan; Martín‐Perea, David M.; Valenciano, Alberto; Hontecillas, Daniel; Montoya, Plini; Morales, Jorge
Abstract : We describe two carnivoran coprolites found in the pseudokarst natural carnivore trap of Batallones‐3, from the Late Miocene of Spain. The larger one, comprising multiple indistinguishable fragments of broken and corroded bones, indicates that the producer of the dropping might have been highly capable of crushing the softer parts of large bones. On the other hand, the smaller one shows several relatively larger and more complete bone fragments, thus exhibiting a greater capacity to break and swallow large portions of bone. The external morphology of the large coprolite is similar to that of extant bears, whereas the smaller one more closely resembles that of the living insectivorous hyaenid Proteles in morphology, on the one hand, and that of the viverrid Genetta in size, on the other hand. We hypothesize that the amphicyonid Magerycion anceps was the producer of the large coprolite and the jackal‐sized basal hyaenid Protictitherium crassum excreted the smaller one. Thus, we present the first direct evidence of a bone durophagous diet in the carnivorans of Batallones.